A Analisis Penggunaan Metode dan Media Pembelajaran pada Materi Hidrokarbon di Tingkat Sekolah Mengengah Atas - Simatupang, Nova Irawati; Naqsyahbandi, Fajar; Wijoyo Mulyopratikno, Fapriyan; Atun, Sri; Arianingrum, Retno (Chemistry Education Practice, 2024)
This research aims to identify and analyze the use of teaching methods and learning media used by chemistry teachers in teaching organic chemistry materials, especially the topic of Hydrocarbons in High School. The research method used is quantitative descriptive research, where to collect data using research instruments in the form of questionnaires distributed using google form to respondents. The respondents were high school chemistry teachers in the Jakarta area who were randomly selected as many as 22 teachers. The results of the analysis show that the teaching method most widely used by teachers on the topic of Hydrocarbons is group discussion which is 20.20% While the learning media most widely used by teachers is molymod media by 23.29% and IT-based learning media by 20.55%. For the utilization of IT / digital media on hydrocarbon material, more use of Ms.Power Point / Prezi / Canva by 34.48% and animated videos by 29.31%. By using learning methods and media used by teachers on the topic of hydrocarbons, it can help students' level of understanding in the range of 60-80 by 64% and more than 80 by 32%.